POLITICAL COMMUNICATION STRATEGIES IN EUROPEAN-LEVEL NEGOTIATIONS: DISCOURSE AND FRAMING IN BART DE WEVER’S ROLE IN THE EUROCLEAR SETTLEMENT - Alan Munandar; Nanda Putri Adila; Novianah Dwi Pratiwi (Universitas Negeri Yogyakarta, 2026)
The European Union’s December 2025 discussions on how to access frozen Russian Central Bank assets held at Euroclear was a modal point in the EU’s assessment of how to pay for Ukraine. This study analyzes the way in which Belgian Prime Minister Bart De Wever was able to utilize strategic political communication to effectively bury the European Commission’s proposed ‘reparations loan’ and nudge consensus towards a €90 billion joint debt financing compromise. Basing on a qualitative analysis of De Wever’s public discourses, media coverage and leaked negotiation papers, the study identifies three main communication mechanisms: legal-financial framing which presented Belgium as defender of International law and financial stability; coalition-building that grouped small and medium size member states (Italy, Bulgaria, Czech Republic, Malta) around shared risk concerns; rhetorical entrenchment by use of historical allusions and metaphorical language to create psychological barriers to compromise. The findings suggest that good political communication can be a resource of real power in multilevel governance contexts, and that smaller and medium-sized states can have a disproportionate influence on crucial European policy outcomes. This is an example in action of the operation of productive power within consensus oriented institutional spaces where legal certainty and rule-of-law principles offer strategic communication opportunities. Challenging conventional IRT, the study shows that material policy effects may only result from discursive power but not from possessing material capabilities.